(3GdaQhb aj GddZIs - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO Hf jMji Hf egQGf, CHh gdGd GdYScQj , J (B395 (3g` s ((3jGbhJ Hf YHO Gddg GdQhei GdMehi s)
(3ChdgG (B:s
(3bhdg ef QMeI adG eeSc dgG s
(3BNQgG (B:s
(3BNQ cJGH GdMQhaq s
(3Vef eLehY , JQJjHgG (B: 3s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B560s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GddZIs